Immobilized Copper Complexes on Coal-Bearing Kaolin for Catalyzing Allylic Ester Synthesis via C(sp3)–H Bond Activation - Chun-Ling Zhang; Dao Su; Habuer Wang; Tegshi Muschin; Yun Wu; Yong-Sheng Bao; Huai-Yong Zhu (Molecules)
Copper complexes have attracted significant interest for catalyzing oxidative dehydrogenative carboxylation of alkanes to form esters. Here, we report a heterogeneous catalyst, in which copper complexes are immobilized on coal-bearing kaolin for the synthesis of allylic esters via C(sp3)-H bond activation through cross-dehydrogenation coupling reactions between cyclic alkanes and aromatic carboxylic acids. Systematic optimization of reaction conditions—including catalyst loading, copper content, oxidant, temperature, and reaction time—resulted in a high yield of 71% of allylic ester, comparable to homogeneous transition metal catalysts. The catalyst is easily recoverable via centrifugation and retains its activity over five consecutive reuse cycles. This system demonstrates broad substrate compatibility with various aromatic carboxylic acids and cyclic alkanes. Beyond offering an efficient and reusable catalytic route for allylic ester synthesis, this work highlights the potential of coal-bearing kaolin as a sustainable support material for transition metal catalysis and provides an environmentally benign method for activating inert C(sp3)–H bonds.